Trends in Incidence of Adolescent Idiopathic Scoliosis: A Modern US Population-based Study. Issue 6 (1st July 2021) - Thomas, Joshua J.; Stans, Anthony A.; Milbrandt, Todd A.; Kremers, Hilal M.; Shaughnessy, William J.; Larson, A. Noelle
Abstract : Background: A successful disease screening strategy requires a high incidence of the condition, efficacy of early treatment, and efficient detection. There is limited population-based data describing trends in incidence of adolescent idiopathic scoliosis (AIS) in the United States and potential role of school screening programs on the incidence of AIS. Thus, we sought to evaluate the incidence of AIS over a 20-year period between 1994 and 2013 using a population-based cohort. Methods: The study population comprised 1782 adolescents (aged 10 to 18 y) with AIS first diagnosed between January 1, 1994 and December 31, 2013. The complete medical records and radiographs were reviewed to confirm diagnosis and coronal Cobb angles at first diagnosis. Age-specific and sex-specific incidence rates were calculated and adjusted to the 2010 United States population. Poisson regression analyses were performed to examine incidence trends by age, sex, and calendar period. Results: The overall age-adjusted and sex-adjusted annual incidence of AIS was 522.5 [95% confidence interval (CI): 498.2, 546.8] per 100, 000 person-years. Incidence was about 2-fold higher in females than in males (732.3 vs. 338.8/100, 000, P <0.05). The incidence of newly diagnosed AIS cases with radiographs showing a Cobb angle >10 degrees was 181.7 (95% CI: 167.5, 196.0) per 100, 000 person-years. The overall incidence of AIS decreased significantly after discontinuation of school screening in 2004 ( P <0.001). The incidence of bracing and surgery at initial diagnosis was 16.6 (95% CI: 12.3, 20.9) and 2.0 (95% CI: 0.5, 3.4) per 100, 000 person-years, respectively. Conclusions: Overall population-based incidence of AIS decreased after school screening was discontinued. However, incidence of patients with a Cobb angle >10 degrees, initiation of bracing and surgery did not change significantly over time. This provides further data to help determine the role of scoliosis screening. Level of Evidence: Level III.